Application design of Chinese multi-pattern fuzzy matching algorithm - Jian Qin (2011 International Conference on Business Management and Electronic Information, 2011)
Directing at the common problems encountered in Chinese Information matching, it is analyzed in this thesis the characteristics and implementation mechanism. As for the characteristic that it is fit for the accurate matching of multi-pattern alphabetic string, we propose to transfer the Chinese information multi-mode fuzzy matching into the algorithm of WM-fitted exact matching. In the course of this algorithm, firstly it does pretreatment to the key word and monitored text in allusion to the diversity of Chinese expressions; then it applies WM algorithm to achieve the Chinese information multi-pattern matching; finally, since the result from exact matching is not the final one, further matching needs to be done to the result gained. This thesis gives a specific introduction to the implementation procedure of the algorithm. The last part gives analysis and does detection to the correctness and implementation efficiency of the algorithm, ended with a satisfactory result.